(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Background: The “anatomical” and “mathematical” methods are the two main types of adult stature estimation methods available. Stature is considered one of the “big four” parameters for profiling individuals in cases of forensic anthropology. However, the most reliable available methods for stature estimation require the preservation of long bones. Lower extremities length assumes a significant part in the assessment of the height of an individual. Aim: Measurement of tibial length to estimate the stature in young adults. Material & Methodology: A correlation study was conducted with the approval from the institutional ethics committee during the period of October 2014 to May 2017 among 500 adults. All the right-handed males and females in the age group of 22–40 years were included in the study. Results: In the study, the mean tibial length in males was 37.04 ± 1.00 cm and in females was 35.30 ± 1.97 cm. Males had an average height of 162.51 ± 7.56 cm, whereas females had an average height of 153.59 ± 5.21 cm. The study also reveals that tibial length is a better predictor among males than females to estimate stature. Conclusion: Tibial length is a reliable measurement for estimating stature with quite a good correlation coefficient value of 0.623.